Risk assessment as a tool to explore sustainable development issues: lessons from the Australian coal industry. (19th June 2007) - Evans, Robin; Brereton, David; Joy, Jim
Risk assessment is a familiar tool in the minerals industry. Originally introduced to explore areas of safety and health in the workplace, the tool is now increasingly used by the industry in other areas such as environmental management. As the industry grapples with the concept of sustainable development, risk assessment represents a potentially useful methodology to engage operations with the broader range of issues involved. However, a limitation of the traditional risk mitigation approach is that it focuses on avoiding negative outcomes, whereas a sustainability focus requires consideration of positive impacts as well. This paper describes an initial attempt to use modified risk assessment methodologies to engage with three Australian coal mining operations on the subject of sustainable development. It describes the rationale for the project, the outcomes from the trials and the overall lessons from the exercise.